2016
DOI: 10.1093/infdis/jiw646
|View full text |Cite
|
Sign up to set email alerts
|

Invariant NKT cells are pathogenic in the HLA-DR4-transgenic humanized mouse model of toxic shock syndrome and can be targeted to reduce morbidity

Abstract: During toxic shock syndrome (TSS), bacterial superantigens trigger a polyclonal T -cell response leading to a potentially catastrophic "cytokine storm". Whether innate-like invariant natural killer T (iNKT) cells, with remarkable immunomodulatory properties, participate in TSS is unclear. Using genetic and cell depletion approaches, we generated iNKT cell-deficient, superantigen-sensitive HLA-DR4-transgenic (DR4tg) mice, which were compared with their iNKT-sufficient counterparts for responsiveness to staphylo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…Such an effect was dependent on SAg pre-exposure, as a contrasting phenotype was seen when SEB was administered following a pre-existing influenza infection, highlighting the potential core differences in how SAgs can function when exposed to naïve or memory virus-specific CD8 + T cells. SAgs possess the ability to bind αβ TCRs on MHC-restricted CD4 + or CD8 + T cells, but also target unconventional, antimicrobial T cell populations bearing αβ TCRs, such as MAIT cells [ 273 , 274 ] and iNKT cells [ 275 , 276 ] ( Figure 3 ). However, SAgs can also recognise γδ T cells, demonstrating that these toxins can bind TCRs lacking TCR α- or β-chains, and such interaction by certain SAgs involves TRGV9 + γδ TCRs [ 277 , 278 , 279 , 280 ].…”
Section: Bacterial Immune Evasion Strategiesmentioning
confidence: 99%
“…Such an effect was dependent on SAg pre-exposure, as a contrasting phenotype was seen when SEB was administered following a pre-existing influenza infection, highlighting the potential core differences in how SAgs can function when exposed to naïve or memory virus-specific CD8 + T cells. SAgs possess the ability to bind αβ TCRs on MHC-restricted CD4 + or CD8 + T cells, but also target unconventional, antimicrobial T cell populations bearing αβ TCRs, such as MAIT cells [ 273 , 274 ] and iNKT cells [ 275 , 276 ] ( Figure 3 ). However, SAgs can also recognise γδ T cells, demonstrating that these toxins can bind TCRs lacking TCR α- or β-chains, and such interaction by certain SAgs involves TRGV9 + γδ TCRs [ 277 , 278 , 279 , 280 ].…”
Section: Bacterial Immune Evasion Strategiesmentioning
confidence: 99%
“…Generally, SAgs have weak affinity for murine MHC class II molecules compared to human HLA molecules [ 97 ]. Using transgenic animals such as the C57BL/6 DR4tg that express the human DR4 HLA allele, SAg mediated disease such as TSS can be modelled as these animals become significantly more sensitive to direct exposure to purified SAgs such as SEB [ 98 ]. These animals can also be utilized in a bacteremia model for SAg expressing strains of S. aureus .…”
Section: Superantigens In S Aureus Pathogenesimentioning
confidence: 99%
“…Considerable efforts have focused on understanding the stimulation of conventional (i.e., MHC-restricted CD4 + and CD8 + ) T cells; however, ‘unconventional’ T cells that harbor unique TCRs also represent important components of the human immune system. These include CD1d-restricted natural killer T (NKT) cells, mucosa-associated invariant T (MAIT) cells and γδ T cells, each of which appear to be activated directly or indirectly by SAgs ( Figure 2 ) [ 98 , 133 , 134 ]. Unconventional T cells, in general, express a less variable TCR compared to conventional T cells, and have rapid effector responses once stimulated.…”
Section: Superantigens In S Aureus Pathogenesimentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of these cell types by SEs can have a considerable impact on the immune system, which may lead to non-conventional overstimulation of the immune system, as exemplified by B cell proliferation and differentiation into plasma cells (Stohl et al, 1994 ). Additionally, excessive inflammation, as a result of the direct activation of i NKT cells and γδ T cells, can cause the production of SE-associated inflammatory disease in the lungs (Rieder et al, 2011 ) and systemic infection, as demonstrated in mouse infection models (Szabo et al, 2017 ).…”
Section: The Enterotoxins Are Immunomodulators Of Multiple Immune Celmentioning
confidence: 99%